Wellbeing of lesbian women in rural areas: an exploratory study - Fernández-Rouco, Noelia (2013)
homosexuality; lesbians; quality of life; wellbeing; ruralHomosexuality, especially in rural areas has been relegated to the background, especially related with women. The aim of this study is to investigate rural homosexual women wellbeing and the relationships between different wellbeing variables in this population. Based on a cross-sectional study semi-structured interviews and scales for different variables related to wellbeing were conducted. The results showed a satisfactory general wellbeing perception, although experience of loneliness is high. Furthermore, relationships between some of the variables studied were founded. This study highlights the importance of research about homosexual women, while reflecting the need for future intervention.